IMPROVING MUSIC ASSEMBLE LEARNING OUTCOMES THROUGH PREZI LEARNING MEDIA FOR CLASS VII-C STUDENTS OF SMP NEGERI 2 PANGURURAN - Nainggolan, Pitriana; Widiastuti, Uyuni (Universitas Lambung Mangkurat, 2024)
The problems in this research include: Minimal use of learning media; teachers only use the lecture method, students are less interested in learning, teachers do not motivate students to learn, so learning outcomes are still low and do not meet the KKM value. Therefore, it is necessary to carry out research with the aim of: finding out the application of Prezi learning media to improve learning outcomes in music ensemble playing material and knowing student learning outcomes after implementing Prezi learning media. The method used in this research is Classroom Action Research (PTK) by collecting qualitative and quantitative data. The results of the research found that: The first cycle learning results of the 28 students who were subjects in the research, 12 students already had complete learning (42.85%), while 13 students had not yet completed the percentage (57.14%) and the average score. -the average obtained was 56.07. The results of the second cycle of learning, 23 students (82.14%) already had complete learning, while 5 students (17.86%) still did not have complete learning. The average value obtained reached 78.21. From the development of the pre-cycle, cycle I and cycle II, it can be seen that there was an increase in learning outcomes in the first learning outcomes test, there were 42.85% of students who achieved learning completeness. In the learning outcomes test II, there were 82.14% of students who achieved learning completeness and there was an increase so it can be concluded that the ensemble music material in Arts and Culture learning by applying the Prezi learning media which was implemented in the pre-cycle, cycles I and II experienced an increase in learning outcomes.